A modified IWAN model for micro-slip in the context of dampers for turbine blade dynamics. (15th April 2019) - Li, Dongwu; Xu, Chao; Liu, Tong; Gola, Muzio M.; Wen, Lihua
Highlights: Proposing a new microslip contact model considering the time-variable normal load. Mechanics of a laboratory under-platform damper is analysed by the new model. Numerical results are validated by experimental results. The effect of micro-slip on under-platform mechanics is identified and highlighted. Abstract: In turbine blade systems, under-platform dampers are widely used to attenuate resonant vibrations and prevent high cycle fatigue failure depending on friction contact. To effectively predict dynamic response of blade-damper system, a numerical model of friction contact between damper and blade is required. The majority of existing friction contact model either cannot reproduce micro-slip behavior or include too many contact parameters, which restricts their application. The proposed model, a modification of the IWAN model, not only describes the tangential micro/gross-slip and normal contact/separation motions, but also has the same number of parameters as the classical gross-slip model. A group of microslip-dominated experimental results for a laboratory crossed curve-flat under-platform damper are shown, and a specially developed procedure is used to determine the elastic contact parameters in order to validate the proposed model. It is shown that the proposed model is able to correctly represent the damper's energy dissipation under low vibration amplitudes. The relative difference of energy dissipation between experiment and simulation by the proposed model is about 1.15%, far less than 24% according to the gross-slip model. Furthermore, the relative simple expression of the model is fully compatible with the current state-of-the-art in the numerical analysis of resonance damping of bladed disks for axial flow turbo-machinery.